2001
DOI: 10.1039/b105016h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structures and properties of platinum(ii) complexes of oligothiophene-functionalized ferrocenylacetylene

Abstract: A series of rigid-rod alkynylferrocenyl precursors with oligothiophene (from thiophene to terthiophene) linkage units in the backbone, [(η 5 -C 5 H 5 )Fe(η, have been prepared in moderate to good yields. The ferrocenylacetylene complexes 4a-4c can be used to form a range of stable platinum() alkynyl and bis(alkynylAll these new compounds have been fully characterized by analytical and spectroscopic methods and the molecular structures of the bithienyl-linked complexes [(η2b, 4b, 5b and 6b have been establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 68 publications
2
28
0
1
Order By: Relevance
“…For the synthesis of trans-[Pt(CϵCFc) 2 (PFc m nBu 3-m ) 2 ] (m = 0, 9a; [47] m = 1, 9b; m = 2, 9c), phosphines 3a-3c were treated with cis-[PtCl 2 (SEt 2 ) 2 ] (6) to form platinum complexes of the type [PtCl 2 (PFc m nBu 3-m ) 2 ] (m = 0, cis-7a; [48] m = 1, trans-7b; m = 2, trans-7c; Scheme 2). The subsequent reactions of 7a-7c with cuprous ferrocenyl acetylide (8) afforded the title compounds 9a-9c (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the synthesis of trans-[Pt(CϵCFc) 2 (PFc m nBu 3-m ) 2 ] (m = 0, 9a; [47] m = 1, 9b; m = 2, 9c), phosphines 3a-3c were treated with cis-[PtCl 2 (SEt 2 ) 2 ] (6) to form platinum complexes of the type [PtCl 2 (PFc m nBu 3-m ) 2 ] (m = 0, cis-7a; [48] m = 1, trans-7b; m = 2, trans-7c; Scheme 2). The subsequent reactions of 7a-7c with cuprous ferrocenyl acetylide (8) afforded the title compounds 9a-9c (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…The platinum acetylide complexes trans-[Pt(CϵCFc) 2 terized by single-crystal X-ray diffraction. Compounds 7b, 7c, 9b, and 9c exhibit a trans arrangement of the ferrocenylphosphine moieties at the platinum center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of polarization functions to C, N and O would increase the number of basis functions by more than a hundred. Previous molecular orbital calculations on other related systems [45,46] showed that the medium-size basis set provides reasonable results. In addition, we are interested in obtaining the qualitative picture of orbital patterns for the clusters and in comparing the relative HOMOϪLUMO gaps.…”
Section: Methodsmentioning
confidence: 99%
“…50 auf und kommen als Modellsysteme für molekulare Drähte infrage. [302] In den letzten Jahren wurde über eine Reihe von MetallFerrocenylalkinylkomplexen unter anderem mit Pt II , [295,303,304] Mn I , [305] Ru und Os, [131,[306][307][308][309][310] [Co 2 (CO) 6 ] [276,311,312] und Titanocen berichtet, [313] aus denen durch chemische oder elektrochemische Oxidation zweikernige gemischtvalente Heterometallkomplexe erhältlich sind. [314] Die Systeme lassen sich nach Robin und Day als gemischtvalente Verbindungen der Klasse II einstufen.…”
Section: Ferrocenylalkineunclassified